Reparative futurities: South African food production and the climate crisis - Wingfield, Matthew (New Agenda: SA Journal of Social and Economic Policy, 2024)
The industrialised food system has both contributed to and will in turn be affected by the climate crisis. In South Africa, as is true globally, the way in which food production has intersected with processes of industrialisation and the green revolution has not only shaped how we relate to food production, but to nature more fundamentally. MATTHEW WINGFIELD explores the emergent possibilities of reimagining and reconstituting how food is produced, based on his case study situated in an agricultural zone on the outskirts of Cape Town called Philippi. It explores alternative ways of interacting with environmental resources that can forge “just” climate futures.